Emerging Role of Spinal Cord TRPV1 in Pain Exacerbation. (14th January 2016) - Choi, Seung-In; Lim, Ji Yeon; Yoo, Sungjae; Kim, Hyun; Hwang, Sun Wook
Abstract : TRPV1 is well known as a sensor ion channel that transduces a potentially harmful environment into electrical depolarization of the peripheral terminal of the nociceptive primary afferents. Although TRPV1 is also expressed in central regions of the nervous system, its roles in the area remain unclear. A series of recent reports on the spinal cord synapses have provided evidence that TRPV1 plays an important role in synaptic transmission in the pain pathway. Particularly, in pathologic pain states, TRPV1 in the central terminal of sensory neurons and interneurons is suggested to commonly contribute to pain exacerbation. These observations may lead to insights regarding novel synaptic mechanisms revealing veiled roles of spinal cord TRPV1 and may offer another opportunity to modulate pathological pain by controlling TRPV1. In this review, we introduce historical perspectives of this view and details of the recent promising results. We also focus on extended issues and unsolved problems to fully understand the role of TRPV1 in pathological pain. Together with recent findings, further efforts for fine analysis of TRPV1's plastic roles in pain synapses at different levels in the central nervous system will promote a better understanding of pathologic pain mechanisms and assist in developing novel analgesic strategies.